Pengaruh E-Promotion Dan E-Wom Terhadap Keputusan Pembelian Busana Adat Bali Di Gianyar (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2025)
Along with today's increasingly sophisticated technological developments, the use of the internet is no longer a new phenomenon, especially in the field of marketing. The digital era has brought about massive changes in consumer behavior, and marketing strategies must adapt accordingly. One of the most notable trends is the rise of online shopping, which has now become the primary choice for many people around the world. This is especially true for individuals with busy lifestyles who do not have enough time to visit conventional or physical stores to purchase the products they need. Through the internet, consumers can browse, compare, and buy products anytime and anywhere, making the shopping process more convenient and efficient. In this study, several data analysis techniques were used to examine the factors influencing purchasing decisions in the context of online shopping. The test instruments applied include validity and reliability tests to ensure the accuracy and consistency of the research instruments. Further, the data analysis methods employed consist of the classical assumption test, multiple linear regression analysis, coefficient of determination (R²), as well as partial (t-test) and simultaneous (f-test) hypothesis testing.Based on the research results, it was found that e-promotion has a positive and significant effect on consumer purchasing decisions. Additionally, electronic word of mouth (E-WOM) also shows a positive and significant influence